The Importance of Islamic Education for The Mental Health of Youth in Using Social Media - Raihan Melisa Lubis; Ira Suryani; Adam Syahputra; Wina Sahila (Nazhruna: Jurnal Pendidikan Islam, 2023)
The purpose of this study was to analyze how the behaviour of adolescents uses social media and to analyze whether there is a relationship between Islamic education and the mental health of adolescents in utilizing social media in Binjai Bakung Village, Deli Serdang Regency. This study uses a quantitative method with a research design cross-sectional. For the sampling technique use the technique of purposive sampling. The population in this study were all young men and women who attended the National Development Education Foundation (PEMNAS) Binjai Bakung, Pantai Labu District, Deli Serdang Regency; in the 2022/2023 school year. While the sample is taken from a population of as many as 240 people. The inclusion criteria in this study were junior high school, high school and vocational school youth who attended the PEMNAS, were willing to be respondents and were on the spot. The collected data was analyzed using SPSS (Statistical Program for Social Science) by testing the level of validity and reliability as well as conducting univariate tests and chi-square tests. Based on the results of statistical testing chi-square with-values0.248> 0.05. This means there is no relationship between social media use and adolescent mental health. This is because most teenagers prefer to access Islamic content as many as 84 people (35%) from 240 people, while teenagers who are interested in accessing entertainment content as many as 33 people (13.8%) from 240 people.